Extrapulmonary tuberculosis in Peninsular Malaysia: retrospective study of 195 cases - Nissapatorn, V.; Kuppusamy, I.; Rohela, M.; Anuar, A.K.; Fong, M.Y. (2004)
During a 2-year retrospective study, 195 non-HIV-infected patients with extrapulmonary tuberculosis (EPT) were diagnosed at the National Tuberculosis Center, Kuala Lumpur, representing 10 of all patients with tuberculosis. Their mean age was 39 (Â±SD) 14 years old (range 14-81). The largest age group was 25-34 years, while 78.5 were less than 50 years of age. The subjects were mainly female (50.3), Malay (49.2), married (61.5), resided in Kuala Lumpur (51.0), and were unemployed (50.3). Regarding risk factors, they were smokers and/or alcohol users (21.0), and injecting drug users (IDUs) (5.1); they also had history of tuberculosis (3.6) and contact with TB patients (9.2). Lymphadenopathy was the most common sign (45.6) shown in the medical records. 42 of x-ray findings (chest, spine, and hip) showed signs consistent with tuberculosis, while histopathology was the most useful diagnostic tool (52.3) and lymph node was the most frequent specimen used (35.0) in this study. The three main sites of involvement were lymph nodes (42.6), miliary and disseminated (19.5), and pleura (12.8). The outcome of this study showed 72.8 of these patients had completed treatment for at least 6 months, whilst, only 4.6 of patients were still undergoing treatment, and unfortunately, 22.6 of them showed non-adherence to anti-tubercular therapy at a duration of less than 6 months. However, no MDR-TB or death cases were reported or registered in this study.